Phenotypes of trpl mutants and interactions between the transient receptor potential (TRP) and TRP-like channels in Drosophila. - Leung, H.T.; Geng, C.; Pak, W.L. (Journal of Neuroscience, 2000)
The trp and trpl genes are thought to encode two classes of light-activated ion channels in Drosophila. A previous report indicated that a null trpl mutant does not display any mutant phenotype. This lack of detectable mutant phenotypes made it difficult to suggest functions for the transient receptor potential-like (TRPL) channel in photoreceptor responses. Here, the properties of trpl photoreceptor responses were studied by using electroretinogram (ERG) and intracellular recording techniques in combination with light stimuli of relatively long durations. Distinct mutant phenotypes were detectable under these conditions. These consisted of a reduced sustained component, oscillations superimposed on the response, a poststimulus hyperpolarization, and altered adaptation properties to dim background light. Comparison of photoreceptor responses obtained from wild type, trp, and trpl showed that the responses obtained from the trp and trpl null mutants did not sum up to that of the wild-type response. To explain the nonlinear summation at the peak of the response, Reuss et al. (1997) proposed that Ca(2+) ions entering through the TRP channel modulate TRP and TRPL channel activities differentially. However, nonlinear summation was present not only at the peak but throughout the duration of response. Two lines of evidence are presented to suggest that, in addition to the interaction proposed by Reuss et al. (1997), there are other forms of interactions between TRP and TRPL channels, probably involving the channel proteins themselves.